Risk Factors for Low Back Pain (LBP) in Tofu Industry Workers in Palembang, Indonesia - Garmini, Rahmi (Poltekkes Kemenkes Tanjung Karang, 2024)
Tofu industry workers are at risk of experiencing Low Back Pain (LBP) because they work with heavy loads and risky work postures for a continuous period of time. The study aims to analyze the relationship between work posture, work period, and knowledge with LBP.: Descriptive analytical research with a cross-sectional design, conducted in Palembang City from March to April 2024. The study involved 40 participants. Data collection was carried out by observation and interviews. Work posture was assessed using the Rapid Entire Body Assessment (REBA) method, while the variables of length of service, knowledge, and LBP were obtained from interviews. All data were analyzed using the Chi-Square test and Prevalence Odds Ratio (POR) at a 95% confidence level. The study found that 17 (42.5%) respondents experienced LBP, 13 (32.5%) had risky work postures, and 22 (55%) respondents had a work period of 6-10 years. The analysis results found that there was a significant relationship between work posture (P= 0.007) and work period (P= 0.010). At the same time, knowledge did not show a significant relationship with LBP (P= 0.167). Risk factors for LBP in tofu industry workers are work posture (POR= 9.524) and work period (POR= 9.750). The study results found that LBP is closely related to work posture and work period. Muscle stretching, getting enough rest, and using ergonomic work tools are research recommendations.